Potential multi-detection manifestation of ultra-sensitive sensors based on ZnO thin films and metamaterials - Defrianto, Defrianto; Soerbakti, Yan; Saktioto, Saktioto; Rini, Ari Sulistyo; Fadhali, Mohammed; Yupapin, Preecha (Science, Technology and Communication Journal, 2024)
This study aims to observe the ability of a thin layer of zinc oxide (ZnO) which is applied to sensor technology. Currently, the low detection limit of the sensor is a problem in its use. Metamaterials offer resonant properties in increasing sensitivity, but their performance is still below the current high modern technology. The high engineering properties of metamaterials provide opportunities for realizing renewable metamaterials. ZnO thin layer semiconductor material as a transparent conductive oxide can provide a wide detection potential. The ability of ZnO thin films to be adapted to metamaterial sensors can be further investigated and improved for the future.